Dekonstruksi Pangan Lokal: Rancang Bangun Susu Tempe Rempah sebagai Produk Gastronomi Berkelanjutan Berbasis Inovasi Pangan Fungsional - Elroy Edgar Waraney Karinda; Diane Tangian; Silvana A. Wewengkang (Lembaga Teewan Journal Solutions, 2026)
This research is motivated by the stigma of tempeh as a lower-class food and the dependence on plant-based milk tied to high-carbon-footprint imported products. This study aims to design a tempeh deconstruction method to produce functional plant-based milk free from beany flavor, and to integrate it as a sustainable gastronomy icon in wellness tourism in North Sulawesi. Using a Research and Development method, the processing involves preparation, extraction and homogenization, local spice infusion, dual filtration, and aeration. Three formulations were sensorially tested using a hedonic scale (1-5) by 26 panelists: F1 (1:3 ratio), F2 (1:4 ratio), and F3 (1:5 ratio). The results show that the optimal formulation is F3 with a 1:5 ratio, achieving a 100% preference level in color, aroma, and taste, and 96.15% in texture. Steaming tempeh for 20 minutes with pandan leaves, along with a strategic increase in local spice concentration, successfully inactivated lipoxygenase enzymes and completely masked the beany aroma. Dual filtration and aeration using a hand frother also succeeded in eliminating coarse fibers, producing a very smooth and light emulsion texture. This innovative product has high commercial potential as a local plant-based milk alternative to support sustainable health tourism.